CHALLENGES AND RESPONSES TO THE IMPLEMENTATION OF ONLINE LEARNING AT A PRIVATE MADRASAH IBTIDAIYAH IN EAST LOMBOK REGENCY - Hadi, Marham Jupri; Abidin, Lalu Abdul Muhyi; Rahmi, Siti; Thohri, Muhammad (Jurnal Ilmiah Mandala Education (JIME), 2022)
The present study aimed at exploring the challenges of online learning practice and the response of students, parents, teachers and Madrassa head during the Covid 19 outbreak. The study employed narrative method involving 2 students, 2 parents of students, 4 teachers and a madrassa head and chairman of the foundation. Data was collected using interviews and participant observation techniques and analyzed using narrative analysis techniques. The results of this study show that online learning practices cannot run optimally due to the lack of learning support facilities and infrastructure such as mobile phones and internet access followed by a lack of readiness of human resources to carry out online learning. Another factor was the lack of parental support for the online learning process caused by low levels of educational awareness and busy work as farm workers and fishermen. The study also revealed that students showed varying responses to online learning while parents, teachers and madrassa head faced many challenges in their implementation.